The Fold-Illuminator: A low-cost, portable, and disposable incubator-illuminator device - Burrington, Logan R. (Synth Syst Biotechnol, 2021)
Fluorescent reporters have revolutionized modern applications in the fields of molecular and synthetic biology, enabling applications ranging from education to point-of-care diagnostics. Past advancements in these fields have primarily focused on improving reaction conditions, the development of new applications, and the broad dissemination of these technologies. However, field and classroom-based applications have remained limited in part due to the nature of fluorescent signal detection, which often requires the use of costly lab equipment to observe and quantify fluorescence readouts. Users without access to laboratory equipment rely on qualitative assessments of fluorescence, a process that remains highly variable from user-to-user even within the same classroom. To overcome this challenge, we have developed a foldable illuminator and incubator device to support field-applications of synthetic biology-based biosensors for education and diagnostics. The Fold-Illuminator is an affordable, portable, and recyclable device that allows for the visible detection of fluorescent biomolecules. The Fold-Illuminator's design allows for assembly in under 10 min, a user can then utilize the optional heating element to incubate biochemical reactions and visualize fluorescence outputs in a defined and light-controlled environment. Interchangeable LED strips and light-filtering screens provide modularity to pair with the fluorescence wavelengths of interest. The user can then unfold the device for convenient storage, transport, or even recycling. The cost for the Fold-Illuminator is $5.58 USD and is compatible with an optional heating element for an additional $3.98 cost, with potential for further reductions in cost for larger quantities. Open-source templates for cutting device parts from paper stock are provided for both printing and cutting by hand; cutting can also be achieved with consumer-grade smart cutting machines such as the Cricut®. Combined with the broad applications of fluorescent reporters, the Fold-Illuminator has the potential to improve access to fluorescence visualization and quantification for new users as well as emerging field applications.